ANALYSIS OF THE EFFECT OF FISCAL DECENTRALIZATION, REGIONAL FINANCIAL PERFORMANCE AND ZAKAT REVENUE ON POVERTY LEVELS IN SUMBAGSEL IN AN ISLAMIC ECONOMIC PERSPECTIVE IN 2018-2024 - Gofur, Abdul; A. Ghofur, Ruslan; Fachri, Adib (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Poverty is a global problem that is still a challenge for many countries, including Indonesia. In 2024, In 2024, as many as 25.22 million people in Indonesia are still classified as poor, indicating that the problem of poverty in Indonesia is still relatively high. This condition also occurs in the South Sumatra region (SUMBAGSEL), where the poverty rate in several provinces is still above the national average. The problem raised in this study is whether fiscal decentralization, regional financial performance and zakat revenue affect the poverty rate in SUMBAGSEL in 2018-2024. The purpose of this study is to determine the effect of these three variables on the poverty rate. With a quantitative research method, the study population includes reports related to all variables in 5 provinces in SUMBAGSEL. The sampling method used is saturated sampling, while the data analysis technique used is panel data using EViews 10 software. The results of the study indicate that fiscal decentralization has no effect on the poverty rate in SUMBAGSEL, while regional financial performance and zakat revenue have a negative and significant effect on poverty.